Identification of a Dental Anomaly in a Tiriyo Indigenous Park Patient by Computed Tomography: A Case Report - de Almeida Rodrigues, PatrÃcia; Ribeiro Ribeiro, Camila; Rodrigues de Freitas, Bianca; Campos Gomes, Thamires; Gaby Neves Rocha, Ellen; Mesquita Tuji, FabrÃcio (Iranian Endodontic Journal, 2019)
This report describes anatomical variations in an indigenous patient from the Brazilian Amazon. A 13-year-old indigenous girl attended the dental clinic for a routine examination. Clinically, a change in the coronary morphology of all upper incisors was observed; characterized by a shovel-shaped lingual surface-a feature considered a polygenic hereditary trait commonly found in native American people. The x-ray examination revealed the presence of a root anomaly in the left upper central incisor. A cone-beam computed tomography (CBCT) scan was performed, revealing the presence of a supernumerary root located on the lingual surface. A single wide canal, which bifurcated in the middle-third level into two canals with different foramina, was observed in the cervical portion. It is essential for dental surgeons to be aware of possible anatomical differences, especially considering the origin of the patient, to avoid interference in treatment success. Keywords: Abnormalities; Cone-beam Computed Tomography; Health Services; Indigenous; Tooth Root